2017
DOI: 10.18632/oncotarget.14756
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of lncRNA NEAT1 in digestive system malignancies: A comprehensive investigation based on 57 microarray and RNA-seq datasets

Abstract: This comprehensive investigation was performed to evaluate the expression level and potential clinical value of NEAT1 in digestive system malignancies. A total of 57 lncRNA datasets of microarray or RNA-seq and 5 publications were included. The pooled standard mean deviation (SMD) indicated that NEAT1 was down-regulated in esophageal carcinoma (ESCA, SMD = −0.35, 95% CI: −0.5~-0.20, P < 0.0001) and hepatocellular carcinoma (HCC, SMD = −0.47, 95% CI: −0.60~-0.34, P < 0.0001), while in pancreatic cancer (PC), NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…27 LncRNA LINC00968 can induce NSCLC development by activating the Wnt pathway. 31 Here, in our study, we found that NEAT1 was significantly increased in GC cells compared with the normal gastric epithelial cells. 29 LncRNA TRERNA1 can promote GC progression by regulating EMT and enhancing SNAI1 expression.…”
Section: Discussionsupporting
confidence: 60%
“…27 LncRNA LINC00968 can induce NSCLC development by activating the Wnt pathway. 31 Here, in our study, we found that NEAT1 was significantly increased in GC cells compared with the normal gastric epithelial cells. 29 LncRNA TRERNA1 can promote GC progression by regulating EMT and enhancing SNAI1 expression.…”
Section: Discussionsupporting
confidence: 60%
“…Whilst many studies implicate the molecule NEAT1 in cancer progression, there are few studies directly connecting paraspeckles, or NEAT1_2, to cancer biology. A meta analysis of NEAT1 in cancer revealed a complex and varying pattern of expression revealing that NEAT1 can be either upregulated, downregulated, or unchanged in tumor compared to normal tissue, depending on different studies and cancer models, with most studies not differentiating between NEAT1 isoforms [50]. Despite this, the possibility for a role for paraspeckles in cancer is gaining more credence.…”
Section: Are Paraspeckles Friend or Foe In Cancer?mentioning
confidence: 99%
“…Our research group has previously performed a comprehensive analysis of the expression levels of NEAT1 in digestive system malignancies based on data from TCGA, GEO, ArrayExpress, and Oncomine [21]. The combined result based on 13 RNA-seq and microarray datasets showed that NEAT1 was downregulated in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have demonstrated that NEAT1 plays essential roles in several malignancies, including breast cancer, lung cancer, laryngeal squamous cell cancer, gastric cancer, nasopharyngeal carcinoma, pancreatic carcinoma, and colorectal cancer [14][15][16][17][18][19][20]. Our research group previously conducted a comprehensive analysis of the clinical value of NEAT1 in digestive system malignancies based on 57 microarray and RNA-seq datasets, ultimately NEAT1 may play different roles in the initiation and progression of digestive system cancers [21]. The biological functions of NEAT1 in HCC have also been investigated in previous studies.…”
Section: Introductionmentioning
confidence: 99%